Dynamics of molecular responses to coxsackievirus B4 infection differentiate between resolution and progression of acute pancreatitis - Gu, Rui (2012)
A coxsackievirus B4 induces acute pancreatitis with different outcomes. The study utilized a systems biology approach to identify molecular immune responses that differentiate between disease resolution and disease progression. The data establish a temporal pattern of host responses that differentiate the resolution of acute pancreatitis from the progression to chronic pancreatitis. A group of twenty-five genes exhibited characteristic expression profiles that were observed during the development of chronic pancreatitis but not during the resolution of disease. We postulate that the temporal dynamics of the twenty-five genes influence the development of pathogenic immune responses associated with chronic pancreatitis. Furthermore, a subset of eleven genes exhibited increased expression as viral titers waned. Of the eleven gene products, five are secreted molecules, TNF-α, IFN-γ, CXCL10, IL-10, and IL-22b, and represent novel potential therapeutic targets since they can be readily modulated with antibodies against the specific cytokine/chemokine or with antibodies against the corresponding receptors.